2005
DOI: 10.2174/092986705774933425
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Inhibition: Targeting Chemical Communication in Gramnegative Bacteria

Abstract: Quorum sensing (QS) systems comprise a new therapeutic target potentially substitutive or complementary to traditional antibiotic treatment of chronic diseases. One route to disrupt the previously established interrelationship between pathogenesis and QS is by blocking the dual functioning signal/receptor transcriptional regulator in some clinically relevant Gram-negative bacteria. The present review contains all reported compound types that are currently known to inhibit the QS transcriptional regulator in Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
61
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 0 publications
0
61
0
Order By: Relevance
“…As a result of the specific binding between signal receptor proteins and their signal molecules, competitive inhibitors that interfere with their interactions have been suggested as potential QS inhibitors that can reduce the formation of harmful biofilms and also increase the susceptibility of many pathogenic microbes to antibiotic treatment as well (Kim et al, 2008;Persson et al, 2005;Tateda et al, 2001). However, a biochemical assay for screening QS inhibitors based on the binding affinity between receptor proteins and their signal molecules was not available until recently because of the difficulty in isolating the signal receptor proteins, including LasR and TraR, which are produced as a complex that is tightly associated with their cognate signal molecules (Kiratisin et al, 2002;Schuster et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the specific binding between signal receptor proteins and their signal molecules, competitive inhibitors that interfere with their interactions have been suggested as potential QS inhibitors that can reduce the formation of harmful biofilms and also increase the susceptibility of many pathogenic microbes to antibiotic treatment as well (Kim et al, 2008;Persson et al, 2005;Tateda et al, 2001). However, a biochemical assay for screening QS inhibitors based on the binding affinity between receptor proteins and their signal molecules was not available until recently because of the difficulty in isolating the signal receptor proteins, including LasR and TraR, which are produced as a complex that is tightly associated with their cognate signal molecules (Kiratisin et al, 2002;Schuster et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence now shows that QSIs targeting LasR can attenuate the pathogenicity of P. aeruginosa (17,25,26). QSI compounds have been obtained from natural sources or by synthesis of AHL analogues or by screening random libraries (reviewed in Ref.…”
mentioning
confidence: 99%
“…For example, macrolides such as azithromycin, which inhibit N-acylhomoserine lactone-mediated quorum sensing but do not inhibit the growth of Pseudomonas aeruginosa, are known to efficiently decrease the symptoms of cystic fibrosis and diffuse panbronchiolitis (57,58). Furthermore, a number of other studies have revealed inhib-itors targeting N-acylhomoserine lactone-mediated quorum sensing of gram-negative bacteria (26,43,50,54,55). In the case of gram-positive pathogens, quorum-sensing inhibitors have been investigated with staphylococci, which have a wellknown regulatory system designated agr (32,41).…”
mentioning
confidence: 99%